EFFECT OF IRRIGATION AND NUTRIENT MANAGEMENT ON GROWTH, YIELD AND EVAPOTRANSPIRATION OF DIRECT-SEEDED AUTUMN RICE (ORYZA SATIVA) UNDER THE AGRO-CLIMATIC CONDITIONS OF ASSAM - BOLLAVENI SATHISH KUMAR,; JADAV CHANDRA DAS, (The Bioscan, 2019)
An experiment was conducted at the Instructional-cum-Research Farm, Assam Agricultural University, Jorhat, during two consecutive summers (Feb-June) seasons of 2017 and 2018. The experiment was laid out in a split-plot design with 3 replications to evaluate the growth, yield and evapotranspiration of rice under moisture and nutrient management practices. Among the 4 irrigation regimes, superior growth (Plant height (23.27% and 22.77%), dry matter accumulation (23.15% and 23.45%) and number of tillers (40.96% and 46.88%)), grain yield (32.90% and 36.22%) and evapotranspiration (12.54% and 29.82%) observed under IW:CPE=1.60 in both the year as compared to rainfed. Among the 5 nutrient management practices, 50% N of RDF + 50% N as FYM + Bio-fertilizers resulted in superior growth (Plant height (7.21% and 9.97%), dry matter accumulation (9.21% and 9.11%) and number of tillers (14.21% and 18.85%)), grain yield (15.24% and 19.50%) and evapotranspiration (8.77% and 8.23%) compared to RDF. Based on results, the irrigation regimes IW:CPE ratio 1.60 (receiving 3 and 4 irrigations in 2017and 2018, respectively) and application of 50% RDF (N) + 50% N through FYM + Bio-fertilizers could be followed for enhancing the growth and yield of direct seeded autumn rice under upland conditions of Assam.